'I Found It!' A smartphone GPS treasure-hunting game in a flipped English class. Issue 2 (4th May 2017) - Freiermuth, Mark R.
ABSTRACT: In this project, 10 female Japanese students in the Advanced Interpersonal Communication course at a Japanese university used smartphone technology and a downloaded application to search for containers (called caches or geocaches) that had been hidden near the university campus by their instructor. The instructor placed different assignments in each of the five hidden caches. These assignments asked students to make two videos: one about their experiences while hunting for the caches and the other made by group decision based upon the assignments discovered in the various boxes. Via their comments, students indicated that they had become intrinsically motivated by their experiences throughout the project. They felt connected to others around the world, enjoyed the processes involved while searching for their assignments and had a rewarding experience making and presenting their videos. Although this project took place in an English as a foreign language setting in Japan, this project is highly recommended for English as a second language teachers in settings where English is spoken extensively outside of the classroom.